2019
DOI: 10.1038/s41467-019-13679-0
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-bearing intermetallic electride as an efficient and stable catalyst for Suzuki cross-coupling reactions

Abstract: Suzuki cross-coupling reactions catalyzed by palladium are powerful tools for the synthesis of functional organic compounds. Excellent catalytic activity and stability require negatively charged Pd species and the avoidance of metal leaching or clustering in a heterogeneous system. Here we report a Pd-based electride material, Y3Pd2, in which active Pd atoms are incorporated in a lattice together with Y. As evidenced from detailed characterization and density functional theory (DFT) calculations, Y3Pd2 realize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 59 publications
0
64
0
Order By: Relevance
“…The results indicated that there is an augmentation on the electron density of anchored Pd from Ti 0.87 O 2 , which was beneficial to promote the C-Br bond cleavage. [39][40][41] The DFT calculation was used further to uncover the electronic property of Pd 1 . The chosen theoretical model was based on a monolayered TiO 2 structure, where the Pd single-atom coordinated with four O atoms of TiO 2 , according to the experimental observations (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that there is an augmentation on the electron density of anchored Pd from Ti 0.87 O 2 , which was beneficial to promote the C-Br bond cleavage. [39][40][41] The DFT calculation was used further to uncover the electronic property of Pd 1 . The chosen theoretical model was based on a monolayered TiO 2 structure, where the Pd single-atom coordinated with four O atoms of TiO 2 , according to the experimental observations (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%
“…These results were consistent with the XANES and XPS analyses, suggesting that the interaction between Pd and Ti 0.87 O 2 enriched the electron density of Pd to an appropriate extent, which was propitious to the chemisorption of the reactant. 41 The catalytic performances of Pd 1 -Ti 0.87 O 2 and the commonly used homogenous Pd catalysts toward the Suzuki reaction were evaluated (Table 1). p-Bromotoluene and excessive phenylboronic acid were employed as the model substrates to evaluate the selectivity and conversion of the title reaction.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, in recent past, nanosized bimetallic alloys have attracted attention of the researchers as they show improved catalytic activity than monometallic catalysts, at nanoscale, due to the electronic and geometrical modications which arise as a consequence of synergic cooperation between the two metals of alloys. [43][44][45][46][47][48][49][50] In the present study, both Pd 9 Te 4 and PdTe are bimetallic alloys in which active Pd atoms are incorporated in a lattice together with Te. 25,26 Hence, these intermetallic phases are likely to offer the advantage of hosting solid active sites.…”
Section: Catalytic Studiesmentioning
confidence: 86%
“…Such alloys include Pd 1 Ni 4 , CuPd, Y 3 Pd 2 , Pd 3 Te 2 and Pd 17 Se 15 . 43,48,52,57,64 The alloy Pd 1 Ni 4 has been graed on carbon nanobers and the resulting system (Pd 1 Ni 4 /CNF) gives only 7% conversion in the reaction of phenylboronic acid and chlorobenzaldehyde aer 5 hours at 80 C using 5 mg of the catalyst (Table 4, entry 1). 52 Its performance is insignicant in comparison to that of palladium telluride alloys in the present study.…”
Section: Catalytic Studiesmentioning
confidence: 99%
“…21 The group of Hosono has been the most active in the search for new (inorganic) electrides with appealing applications, but other groups have recently joint the quest. Nowadays, there is a large collection of electrides, which can be classified in terms of the shape of the lattice voids where electrons are trapped: zero-dimensional electrides, 22 one-dimensional electrides, [23][24][25][26] two-dimensional electrides, [27][28][29][30][31][32][33][34] three-dimensional ones, [35][36][37][38][39][40] and electride nanoparticles. 41,42 In Table 1, we have collected all the experimental realizations of electrides, indicating which of them are stable at room temperature, whether they are organic or inorganic, and the number of dimensions of the isolated electron cavity.…”
Section: Introductionmentioning
confidence: 99%